CAN CAPITAL SCARCITY HELP AGENCY THEORY EXPLAIN FRANCHISING? REVISITING THE CAPITAL SCARCITY HYPOTHESIS. - Combs, J. G.; Ketchen, D. J. (Academy of Management Journal, 1999)
We offer a rationale for a link between capital scarcity and franchising. Predictions respectively based on agency theory and the capital scarcity hypothesis were tested among 91 restaurant chains....